CENTER-ing Black voices: incorporating lived experience across the research process to advance equity in drug treatment and outcomes - Devin E. Banks; Maria E. Paschke; Kaytryn D. Campbell; Daje D. Bradshaw-Glenn; Rashmi Ghonasgi; Burton Barr; Arial Collins; Gerald Dennis; Keith Lofton; Alfred Long; Harriet Montgomery; Andreas Prince; et al. (Harm Reduction Journal)
Abstract Background Black people in the United States face persistent and increasing inequities in addiction treatment access and drug overdose death. Incorporating people with lived experience through community based participatory research (CBPR) approaches can improve understanding of drivers of and solutions to such inequities. However, practical and systemic challenges limit incorporating Black people with lived experience with substance use across each step of the research process. This paper describes the methods, recommendations, and lessons learned from a research team and Black-led community advisory board (CAB) working together across the research process to promote equity in harm reduction and addiction treatment. Methods The CENTER Initiative is an academic—community partnership established to address increasing drug overdose deaths affecting the Black community in St. Louis, Missouri. The CAB comprised 10 Black people with lived experience recruited with the help of community-based agency partners. Academic staff dedicated to liaising with the CAB encouraged establishing structure and bylaws toward a self-governing CAB with decision-making power independent of agency partner and research teams. Results The CAB and research team collaborated across all stages of the research process including design (e.g., deciding inclusion criteria), recruitment (e.g., flier development and participant referrals), data collection (e.g., conducting qualitative interviews), analysis (e.g., qualitative coding), and dissemination. Aligned with CBPR principles, dissemination activities extended the impact of the research to create sustainability and community empowerment (e.g., through advocacy, direct intervention, capacity building, and funding). Key lessons learned for working with a CAB facing intersectional oppression include a balanced approach incorporating structure and flexibility, a need for adequate personnel and funding support, and the importance of relationship building. Conclusion Integrating people with lived experience into the research process through CBPR can mitigate the harms and inefficiencies of research while enhancing its community impact. The CENTER CAB and research partners creatively collaborated across each step of the research and translated their findings to practical community empowerment and sustainability in innovative ways. Research institutions, funders and other stakeholders must support building relationships and capacity among academics and people with lived experience to advance racial health equity and justice in substance use research and outcomes.